TREATMENT OF OVER ERUPTED UPPER RIGHT LATERAL INCISOR ASSOCIATION WITH PATHOLOGIC MIGRATION IN CHRONIC PERIODONTITIS - , Ade Ismail A. K. ([Yogyakarta] : Fak.Kedokteran Gigi Universitas Gadjah Mada, 2012)
Background.Theoccurrenceof Pathologictooth migration(PTM)amongperiodontaldiseasewere high. It isalsoa common complication following moderate to severe chronic periodontitis and more often become the motivation for patient to seek periodontal therapy. PTMwas categorized into facial flaring, diastema, rotation, extrusion and drifting of the teeth. Inthe caseof earlyto moderatchronicperiodontitis,spontaneouscorrectionof PTMoccursafter conventional periodontal therapy. However, in the case of severe chronic periodontitis, spontaneous correction are less likelytooccur. The purpose. Thecase report is repositioning the over erupted upper right lateral incisor, minlmalizingthe tooth mobility and to overcome patient's esthetic problem. Case. 49 years old female complain about the lateral incisor mobility and become extruded (over eruption) that disturbing her appearance and want to fixed it. The lower labial segment showed mild crowding whilst the upper labial segment demonstrated mobility and over eruption of lateral incisor. Treatment was thus limited to the upper arch with orthodontic splint following konvensional periodontal therapy, scaling &amp